2-[(1E,3E)-4-Arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones as dienes in Diels-Alder reactions - experimental and computational studies - Albuquerque, Hélio (2017)
The synthesis and reactivity of 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones as dienes in Diels–Alder (DA) reactions with several electron-poor and electron-rich dienophiles under microwave irradiation was studied. The optimized reaction conditions were achieved with N-methylmaleimide as the dienophile and Sc(OTf )3 (OTf = triflate) as a Lewis acid under microwave-assisted and solvent-free conditions. The Lewis acid improved the reaction yields as it prevented the adducts obtained from undergoing a second DA reaction; thus, the formation of a bisadduct was avoided. The α, :γ,δ-diene of the starting chromones was the most reactive, and the computational results confirmed the experimental findings. Theoretical calculations also provided a rationale for the unexpected lack of reactivity shown by some dienophiles. The adducts prepared were dehydrogenated with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ); however, the aza adducts were sensitive to the highly energetic reaction conditions necessary for the aromatization.